11.15 ABN survey 2016: geographic variations in service provision. Issue 12 (14th November 2019) - Fernandes, Peter; Mummery, Cath
Abstract : Introduction: The 2016 ABN Acute Neurology survey provides a wealth of data on geographic variations in the provision of neurological services. In this abstract we discuss differences in access to neurological care and services with respect to the 19 ABN regions. Methods: 2016 ABN survey data were analysed by region with bed data obtained from ONS records. Missing data were checked where possible but otherwise assumed to be negative responses. Results: Across the UK there are 263 beds/FTE consultant, ranging from 455 (Wales) to 154 (SW Thames). Neurology inpatients as a proportion of total patients differ 16-fold between South West (0.016) and Wales (0.001). There are wide variations in acute neurological services (ward consultants, acute clinics, MAU ward-rounds). Only East Anglia and Northern Ireland regions have on-site stroke thrombolysis in all hospitals. Involvement in acute stroke thrombolysis ranges from 2.5 neurology consultants/hospital (Wessex) to 0 (NW Thames and Mersey). Access to investigations differs widely for 24/7 MRI (35% all hospitals, regional ranges 0% to 83%); EEG (61% [38%-85%]); NCS/EMG (57% [20%-85%]); and on-site neuro-radiology (38% [17%-71%]). Conclusion: These data show considerable differences in a variety of metrics between ABN regions, with implications for equitability of care.